Ex vivo Improvement of a von Willebrand Disease Type 2A Phenotype Using an Allele-Specific Small-Interfering RNA - de Jong, Annika; Dirven, Richard J.; Boender, Johan; Atiq, Ferdows; Anvar, Seyed Yahya; Leebeek, Frank W. G.; van Vlijmen, Bart J. M.; Eikenboom, Jeroen (Thrombosis and Haemostasis, 2020)
Von Willebrand disease (VWD) is the most common inherited bleeding disorder and is mainly caused by dominant-negative mutations in the multimeric protein von Willebrand factor (VWF). These mutations may either result in quantitative or qualitative defects in VWF. VWF is an endothelial protein that is secreted to the circulation upon endothelial activation. Once secreted, VWF multimers bind platelets and chaperone coagulation factor VIII in the circulation. Treatment of VWD focuses on increasing VWF plasma levels, but production and secretion of mutant VWF remain uninterrupted. Presence of circulating mutant VWF might, however, still affect normal hemostasis or functionalities of VWF beyond hemostasis. We hypothesized that inhibition of the production of mutant VWF improves the function of VWF overall and ameliorates VWD phenotypes. We previously proposed the use of allele-specific small-interfering RNAs (siRNAs) that target frequent VWF single nucleotide polymorphisms to inhibit mutant VWF. The aim of this study is to prove the functionality of these allele-specific siRNAs in endothelial colony-forming cells (ECFCs). We isolated ECFCs from a VWD type 2A patient with an intracellular multimerization defect, reduced VWF collagen binding, and a defective processing of proVWF to VWF. After transfection of an allele-specific siRNA that specifically inhibited expression of mutant VWF, we showed amelioration of the laboratory phenotype, with normalization of the VWF collagen binding, improvement in VWF multimers, and enhanced VWF processing. Altogether, we prove that allele-specific inhibition of the production of mutant VWF by siRNAs is a promising therapeutic strategy to improve VWD phenotypes.
Keywords: von Willebrand disease; von Willebrand factor; small-interfering RNAs; hemostasis